2018
DOI: 10.1088/1748-9326/aab908
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic model-based N management reduces surplus nitrogen and improves the environmental performance of corn production

Abstract: The US Midwest is the largest and most intensive corn (Zea mays, L.) production region in the world. However, N losses from corn systems cause serious environmental impacts including dead zones in coastal waters, groundwater pollution, particulate air pollution, and global warming. New approaches to reducing N losses are urgently needed. N surplus is gaining attention as such an approach for multiple cropping systems. We combined experimental data from 127 on-farm field trials conducted in seven US states duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Several tactics have been proposed to increase NRE crop by improving the synchrony between fertilizer N addition and crop N uptake. These include at-planting application or split application of N fertilizer between pre-plant and early-vegetative growth (Randall and Sawyer, 2008), subsurface placement of N fertilizer (Nkebiwe et al, 2016), inseason diagnostic tools to fine-tune N rate according to weather and soil conditions (Colaço and Bramley, 2018;Sela et al, 2018), enhancedefficiency fertilizers (Li et al, 2018), and enhanced efficiency crops with deep, vigorous root systems (Yu et al, 2015). Gardner and Drinkwater (2009) evaluated the impact of several of these management tactics using meta-analysis and found that they increased NR crop by −0.9 to 43%.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Several tactics have been proposed to increase NRE crop by improving the synchrony between fertilizer N addition and crop N uptake. These include at-planting application or split application of N fertilizer between pre-plant and early-vegetative growth (Randall and Sawyer, 2008), subsurface placement of N fertilizer (Nkebiwe et al, 2016), inseason diagnostic tools to fine-tune N rate according to weather and soil conditions (Colaço and Bramley, 2018;Sela et al, 2018), enhancedefficiency fertilizers (Li et al, 2018), and enhanced efficiency crops with deep, vigorous root systems (Yu et al, 2015). Gardner and Drinkwater (2009) evaluated the impact of several of these management tactics using meta-analysis and found that they increased NR crop by −0.9 to 43%.…”
Section: Management Implicationsmentioning
confidence: 99%
“…McLellan et al (2018) recently suggested N balance, which is a simple input-output based metric defined as the amount of N applied to a production unit minus the amount of N removed from the field at harvest. N balance is readily calculated across different scales and is a good predictor of potential N pollution (Van Groenigen et al 2010, McLellan et al 2018, Sela et al 2018b. It was found to positively correlate with both N leaching Butterbach-Bahl 2014, Zhao et al 2016) and gaseous N losses (Van Groenigen et al 2010, Venterea et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was found to positively correlate with both N leaching Butterbach-Bahl 2014, Zhao et al 2016) and gaseous N losses (Van Groenigen et al 2010, Venterea et al 2016). Although relations between N balance and N losses are notoriously noisy, several studies suggested a nonlinear increase in N losses and possible critical threshold values ranging from 0 to 50 kg ha −1 for different production environments (Van Groenigen et al 2010, Venterea et al 2016, Zhao et al 2016, Sela et al 2018b. This characteristic makes N balance useful for policies that aim to reduce N losses or track progress toward sustainability goals.…”
Section: Introductionmentioning
confidence: 99%
“…increases production costs and causes environmental degradation when unutilized N is lost from fields through denitrification, volatilization, leaching, and runoff (Banger et al, 2020;Rasouli et al, 2014;Sela et al, 2018;Tian et al, 2016). Thus, optimizing N supply to meet crop demands becomes critical due to both economic and environmental concerns (Banger et al, 2020;Ewing & Runck, 2015).…”
mentioning
confidence: 99%